Linguagem cartográfica e estudo do meio: olhares e formas de expressar o espaço geográfico - Costa, Christiane Fernanda da [UNESP]; Pezzato, João Pedro [UNESP]; Osti, Andréia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Propose a didactic sequence to study the location for students of the 3rd grade of elementary school of a public school in Rio Claro, São Paulo, Brazil, it was the central goal of this work. In the context of reading and writing experiences, highlighting the teaching of school cartography, they were involved 58 students. In 2014, during the ten meetings in each of the two rooms, they were produced texts, pictures and sounds in different languages. The material, recorded, classified and compiled, is now part of a database for analysis. An outline of the activities carried out in this project discusses a study of the medium, is conducting a path by the spatial formation history of the city. Such experience may point the wealth of activity that integrated community school, undergraduate and graduate students and university researchers. In this sense, it highlights the importance of projects that articulate the research, teaching and extension. Academic activities that create links with other social institutions, particularly public schools, can be fruitful for teaching and research at different levels of complexity and training processes.

Propor uma sequência didática para o estudo da localidade para alunos do 3º ano do ensino fundamental de uma escola pública municipal de Rio Claro, estado de São Paulo, Brasil, foi o objetivo central do presente trabalho. No contexto de experiências de leitura e de escrita, com destaque para o ensino da cartografia escolar, estiveram envolvidos 58 discentes. Em 2014, durante os dez encontros em cada uma das duas salas, foram produzidos textos, imagens e sons por diferentes linguagens. O material, registrado, classificado e compilado, passou a compor um banco de dados para serem analisadas. Um recorte das atividades realizadas nesse projeto discute um estudo do meio, trata da realização de um trajeto pela história de formação espacial do município. Tal experiência pode apontar a riqueza da atividade que integrou escolares da comunidade, discentes de graduação e pósgraduação e pesquisadores da universidade. Nesse sentido, é destaca a importância de projetos que articulam a pesquisa, o ensino e a extensão. Atividades acadêmicas que criam vínculos com as demais instituições sociais, em especial as escolas públicas, podem ser fecundos para o ensino e para a pesquisa em diferentes níveis de complexidade e processos formativos.
Keywords: Cartographic language; Elementary school; Geography; County; Linguagem cartográfica; Ensino fundamental; Geografia